2011
DOI: 10.1021/cm2021966
|View full text |Cite
|
Sign up to set email alerts
|

Shape Control of Ag Shell Growth on Au Nanodisks

Abstract: Core−shell (Au@Ag) bimetallic nanoparticles containing a Au nanodisk in the core were synthesized using Au nanodisks as seeds. The growth direction of the Ag shell on the gold nanodisks could be tuned by the presence of iodide ions. Without the I − ions, the Ag shell was formed homogeneously over the entire surface of the flat Au nanodisks, while the presence of I − induced the selective coating of the Ag shell in the direction perpendicular to the basal plane of the nanodisks. The resulting core−shell (Au@Ag)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
53
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 22 publications
3
53
0
Order By: Relevance
“…Furthermore, the optical properties of the bimetallic nanoparticles could be fine tuned with the overgrowth of Ag shells. Hong et al reported the shape control of Ag shell growth on Au nanodisks [25]. They found that the presence of iodide ions could greatly affect the growth direction of the Ag shell on the Au nanodisks.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the optical properties of the bimetallic nanoparticles could be fine tuned with the overgrowth of Ag shells. Hong et al reported the shape control of Ag shell growth on Au nanodisks [25]. They found that the presence of iodide ions could greatly affect the growth direction of the Ag shell on the Au nanodisks.…”
Section: Introductionmentioning
confidence: 99%
“…The prepared Au-Ag core-shell nanoparticles display very abundant and distinct LSPR characteristics, which are dependent on core shape and core size. By using iodide ions, the growth direction of the Ag shell on the gold nanodisk core could also be tuned, and then the shape of the coated Ag shell could also be controlled [15]. The LSPR and SERS response in Au dumb bells with silver coating have also been reported [9]; this type of core-shell Au-Ag nanostructure is expected to serve as excellent SERS substrates because of the higher enhancement factors for silver as compared to gold.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, bimetallic core-shell nanostructures have been studied actively for their tunable and identical optical properties, which results from a synergy effect and the intrinsic properties of two components, depending on their final structures [1][2][3][4][5][6][7][8][9][10][11][12]. Among them, Au@Ag core-shell nanostructures are one of the most favorable structures due to quite similar lattice parameters between two components (Au-4.086 Å, Ag-4.078 Å) [13][14][15][16][17][18]. Therefore, it is relatively easy to make the Ag shell on the surface of the Au core and the final morphologies of the nanostructures would be decided by the shape of the Au core.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, unusual Au@Ag dodecahedron and elongated polyhedron Au@Ag nanostructures were synthesized by using circular-shape Au nanoplates in the presence of iodide ions. Without the I À ions, the Ag shell was formed homogeneously over the entire surface of the Au seed [18].…”
Section: Introductionmentioning
confidence: 99%